Who is the 'Journal Grand Master'? A new ranking based on the Elo rating system - Robert Lehmann; Klaus Wohlrabe (Center for Economic Studies and ifo Institute (CESifo), 2016)
In this paper we transfer the Elo rating system, which is widely accepted in chess, sports and other disciplines, to rank scientific journals. The advantage of the Elo system is the explicit consideration of the factor time or the history of a journal's performance. Most other rankings that are commonly applied neglect this fact. The Elo ranking approach can easily be applied to any metric, published on a regular basis, to rank journals. We illustrate the approach using the SNIP indicator based on citation data from Scopus. Our balanced panel consists of 7,748 journals from many scientific fields for the period from 1999 to 2015. We show that the Elo approach produces a similar but not identical ranking compared to other rankings based on the SNIP. Especially the rank order for rather 'middle-class' journals can tremendously change.
Keywords: A12; A14; 330; Elo rating system; journal rankings; SNIP